2020
DOI: 10.1159/000511103
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors, Cognitive Dysfunction, and Mild Cognitive Impairment

Abstract: <b><i>Objectives:</i></b> The present study sought to evaluate the contribution of cardiovascular risk factors to cognitive functioning in a sample of Mexican Americans diagnosed with mild cognitive impairment (MCI). <b><i>Methods:</i></b> Hypertension, diabetes, dyslipidemia, and obesity were diagnosed based on self-report and/or standardized procedures. Cognitive function was measured with MMSE, Logical Memory I and II, Trail A &amp; B, FAS, animal naming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In our study, the level of cognitive impairment was influenced by the co-occurrence of diabetes and dyslipidemia and possibly by the association of other cardiovascular risk factors. Vintimilla et al [ 7 ] studied the impact of cardiovascular risk factors on cognitive status in a Mexican cohort of 515 patients using several tests to measure global cognition of the MMSE. They found that when diabetes and dyslipidemia were present, this affected the ability to think, reason, and remember [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the level of cognitive impairment was influenced by the co-occurrence of diabetes and dyslipidemia and possibly by the association of other cardiovascular risk factors. Vintimilla et al [ 7 ] studied the impact of cardiovascular risk factors on cognitive status in a Mexican cohort of 515 patients using several tests to measure global cognition of the MMSE. They found that when diabetes and dyslipidemia were present, this affected the ability to think, reason, and remember [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mild cognitive impairment (MCI) have an increased risk of developing cardiovascular risk factors (CVRFs) [ 6 ]. The impact of CVRFs, such as diabetes mellitus, dyslipidemia, obesity, and hypertension, on cognition exists [ 7 , 8 ]. However, the physiopathology of CVRFs in patients with mild cognitive impairment is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that cardiovascular risk factors like hypercholesterolemia and hypertension are key factors in the development of mild cognitive impairment, and therefore, measures to control these two conditions in primary care should be reinforced to stop the development of dementias [7,8]. A similar study [9] provided additional evidence for the link between cardiovascular risk factors and cognitive dysfunction in mild cognitive impairment subjects and demonstrated that comorbid risk factors increased the degree of cognitive deficit, indicating a higher risk of developing dementia.…”
Section: Association Between Cardiovascular Comorbiditiesmentioning
confidence: 99%
“…Vascular contributions to cognitive impairment and vascular dementia are characterized by the aging neurovascular unit facing and failing to cope with biological damages caused by systemic and cerebral vascular disease, proteinopathy including Alzheimer's biology, metabolic disease, or immune response, resulting in cognitive decline [8,9]. Atherosclerosis has been described as a predictor of cognitive impairment [10] and has the potential as a drug target to prevent or delay the onset and progression of dementia in older adults.…”
Section: Association Between Cardiovascular Comorbiditiesmentioning
confidence: 99%
“… 4 , 5 The concept of cognitive decline as a vascular disease is being increasingly accepted, 6 together with the evidence that the early detection and treatment of classical cardiovascular risk factors could reduce the impact of cognitive decline. 7 , 8 , 9 In this framework, the monitoring of subclinical cardiovascular risk markers may have an important role in detecting individuals at risk to develop cognitive impairment 9 and in tracking changes induced by treatments. 10 A number of structural alterations that are an expression of vascular aging, reflecting the integrated burden of known and unknown cardiovascular risk factors on the vasculature, such as large artery stiffness 11 , 12 , 13 and carotid structural changes, 14 , 15 have been associated with a steeper cognitive decline.…”
mentioning
confidence: 99%